Movement onstage and off - Barton, Robert 1945-; Sellers-Young, Barbara ca. 20./21.Jh (Routledge, 2017)
"Movement: Onstage and Off is the complete guide for actors to the most effective techniques for developing a fully expressive body. It is a comprehensive compilation of established fundamentals, a handbook for movement centered personal growth and a guide to helping actors and teachers make informed decisions for advanced study." -- Back cover
Keywords: Bewegung; Schauspielkunst; Movement (Acting); Übungssammlung